The ultimate guide to weight training for triathlon - Price, Robert G., ....- (2005)
"The Ultimate Guide to Weight Training for Triathlon is the most comprehensive and up-to-date triathlon-specific training guide in the world today. It contains descriptions and photographs of nearly 100 of the most effective weight training, flexibility, and abdominal exercises used by athletes worldwide. This book features year-round triathlon-specific weight-training programs guaranteed to improve your performance and get you results. No other triathlon book to date has been so well designed, so easy to use, and so committed to weight training. This book was designed specifically for triathletes to increase strength, speed, endurance, and stamina. This guide will have you shaving time off of all three events by using the most advanced and efficient exercises available. It will have you recording new personal records and reaching all of your goals. By following the year-round programs in the book, you will be able to finish meets with the same energy you exerted when you began. Both beginners and advanced athletes and weight trainers can follow this book and utilize its programs. From recreational to professional, thousands of athletes all over the world are already benefiting from this book and its techniques, and now you can too!"
Maximize your athletic potential! - in-season and off-season sport-specific programs designed to: increase speed, eliminate fatigue, and prevent injuries - Triatlon
Keywords: Triatlon ; krachttraining